Pembelajaran Arab Melayu dan Pengaruhnya Terhadap Pembentukan Karakter Siswa di Sekolah Dasar Kabupaten Pidie, Aceh - A. Samad, Sri Astuti (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2018)
The current character crisis is a crucial issue amidst global cultural hegemony that has a negative impact. As a result children experience capital decadence, consumerism, free sex and increased crime. Therefore, it is necessary to study how children get character education that can face the global challenge. This study discusses the problem of learning Malay Arabic Book (Arab Melayu) in Primary School in Pidie District using Halaqah method (teacher reading listening students) and peer tutoring. While the books used are; Book of Tawhid, Book of Akhlak, Bidayatul Muhtadi (fiqih), Masaail Muhtadi (fiqih). This learning process then gave birth to student characters such as; strengthening tauhid, diligent worship, obedient to the teacher, obedient to the parents. Obstacles encountered related to learning methods and learning time that can be solved by teachers together.